Relation between psychological strain and carotid atherosclerosis in a general population. Issue 4 (16th March 2005) - Wolff, B; Grabe, H J; Völzke, H; Lüdemann, J; Kessler, C; Dahm, J B; Freyberger, H J; John, U; Felix, S B
Abstract : Objective: To investigate the hypothesis that psychological strain is related to carotid atherosclerosis in a large general population sample. Methods: Intima–media thickness and the prevalence of atherosclerotic plaques in the carotid arteries were quantitatively assessed by high resolution ultrasound among 2164 participants (1112 women and 1052 men, aged 45 to 75 years) of the SHIP (study of health in Pomerania), an epidemiological survey of a random sample of the population of north eastern Germany. Psychological strain was measured by 13 items reflecting typical psychological complaints. Each item was graded by the study participants on a four point scale (from 0, absent, to 3, severe) and a psychological strain score was generated by summing these 13 items. Results: Mean psychological strain score was 10.8 (7.0) (median score 10) among women and 8.5 (6.2) (median score 8) among men. Psychological strain did not predict carotid intima–media thickness among either men or women. However, after adjustment for covariates, high psychological strain and carotid plaques were independently and linearly related, with plaque prevalence odds of 1.03 (95% confidence interval (CI) 1.01 to 1.05, p  =  0.009) per increment of the psychological strain score among women and 1.04 (95% CI 1.01 to 1.07, p  =  0.003) among men. Conclusions: This study identified a relation between general psychological strain and carotid atherosclerosis.